Desenvolvimento colaborativo de intervenções em saúde mental para aplicativo (APP Mental) direcionado ao cuidado do profissional de saúde no contexto de pandemia (COVID-19) e situações de desastre - Antonialli, Karina Toledo da Silva (2022)
Mental health is considered a public health issue due to the significant prevalence of mental disorders and social and economic impacts. Disasters and pandemics are related to a worsening of mental distress in the general population and, especially, in health professionals. In these moments, it is necessary to implement actions, quickly and effectively, that can prevent or mitigate the mental distress of these workers. In this context, use of tools, such as mobile applications, can be an alternative. This study aims to analyze the experience of health professionals with the mental health prevention and promotion interventions offered by APP Mental, which will contribute to the collaborative development of the app. For this, method, divided into two stages, is proposed: creation of the interventions by a multidisciplinary team and evaluation of this product by users. In the first stage, the multidisciplinary group created a script to guide the development and this team produced thirty-two interventions, in eight thematic areas, which were validated by a committee of experts. This material was adapted to web language and revised for language adaptations before being integrated into the application. In the second stage, health professionals used the Mental APP for twelve weeks, during which they evaluated the interventions with scores from one to five and comments. After this period, they were invited to participate in a focus group to share their experience with the APP Mental. From this meeting and the researchers' impressions, a report was created. This document was validated by the focus group participants. These data were categorized and used for thematic analysis, which resulted in two thematic groupings: 1) the care of yourself and the other, and 2) tool qualification. In the first, we find an intensification of mental distress during the pandemic, the need for embracement, for contact between workers and legitimization of the work process centered on a care technical model based on soft technologies. In the second, for APP Mental users, this mobile application has the potential to promote health care and they suggested some improvements to attract more users, maintain motivation and engagement through the expansion of thematic areas, notification mechanisms and customization. The conclusion is that there is a need for more studies that address digital health, and the data presented in this study contribute to this discussion, highlighting the possibility of using digital technologies as a care strategy linked to the health policies of health workers.